2019
DOI: 10.1002/adem.201900813
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mechanical Properties and Wettability of TiO2NT Arrays Formed in Simulated Body Fluid‐Based Electrolyte

Abstract: Modified titanium nanotubes (TiO2NTs) coatings are grown in simulated body fluid (SBF) from Ticp and Ti6Al4V. The addition of 1% v/v of SBF to the electrolyte neither modifies film morphology nor the structural oxide characteristics for both metal substrates. However, an improvement in mechanical properties (hardness and elasticity model) and wettability is observed. From bioactive assay, a higher amount of fluorapatite was detected on the top of TiO2NTs prepared in SBF‐based electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A previous study showed that SBF promotes pronounced effects on the increase in mechanical properties and wettability of nanotextured titanium dioxide coatings [27].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study showed that SBF promotes pronounced effects on the increase in mechanical properties and wettability of nanotextured titanium dioxide coatings [27].…”
Section: Discussionmentioning
confidence: 96%
“…Structural analysis was carried out by x-ray Diffraction (Higaku 600 Benchtop) with Cu Kα=1.5406 Å and radiation at 40 kV and 150 mA. The phase percentage was also extracted, as similarly reported in Simon et al [27].…”
Section: Titania Nanotubes Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation